Effects of Au Nanoparticle Addition to Hole Transfer Layer in Organic Photovoltaic Cells Based on Phthalocyanines and Fullerene - Akihiko Nagata; Takeo Oku; Tsuyoshi Akiyama; Atsushi Suzuki; Yasuhiro Yamasaki; Tomohiro Mori (Journal of Nanotechnology)
Phthalocyanines/fullerene organic photovoltaic cells were fabricated and characterized. Effects of Au nanoparticle addition to a hole transfer layer were also investigated, and power conversion efficiencies of the photovoltaic cells were improved after blending the Au nanoparticle into PEDOT:PSS. Nanostructures of the Au nanoparticles were investigated by transmission electron microscopy and X-ray diffraction. Energy levels of molecules were calculated by molecular orbital calculations, and the nanostructures and electronic property were discussed.